2015
DOI: 10.1016/j.aap.2015.08.013
|View full text |Cite
|
Sign up to set email alerts
|

Multilevel models for evaluating the risk of pedestrian–motor vehicle collisions at intersections and mid-blocks

Abstract: Walking is a popular form of physical activity associated with clear health benefits. Promoting safe walking for pedestrians requires evaluating the risk of pedestrian-motor vehicle collisions at specific roadway locations in order to identify where road improvements and other interventions may be needed. The objective of this analysis was to estimate the risk of pedestrian collisions at intersections and mid-blocks in Seattle, WA. The study used 2007-2013 pedestrian-motor vehicle collision data from police re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(43 citation statements)
references
References 73 publications
0
43
0
Order By: Relevance
“…Traffic Volume: Traffic volume, whether represented directly by measures such as vehicle miles travelled or indirectly by arterial road presence, is one of the strongest risk factors associated with PMVCs. Research has consistently shown that areas with higher traffic volume result in more PMVCs, as well as higher injury severities [15][16][17][18][19][20]. This effect is not necessarily distributed uniformly in space.…”
Section: Risk Factorsmentioning
confidence: 99%
See 3 more Smart Citations
“…Traffic Volume: Traffic volume, whether represented directly by measures such as vehicle miles travelled or indirectly by arterial road presence, is one of the strongest risk factors associated with PMVCs. Research has consistently shown that areas with higher traffic volume result in more PMVCs, as well as higher injury severities [15][16][17][18][19][20]. This effect is not necessarily distributed uniformly in space.…”
Section: Risk Factorsmentioning
confidence: 99%
“…Road Width: Closely related to traffic volume is road width, which can be examined as the number of lanes as well as the width of those lanes. With regard to the former, numerous studies have found that the number of lanes on a road is significantly associated with increased risk of PMVC [15,18,22,23]. This is due to the added distance that pedestrians are required to cross, thereby increasing their exposure to traffic.…”
Section: Risk Factorsmentioning
confidence: 99%
See 2 more Smart Citations
“…This is mainly done to evacuate the traffic congestion and accidents at peak hours. approach which uses the data about the characteristics of road and the surroundings of neighbourhood [5].…”
Section: Introductionmentioning
confidence: 99%